Large-size electric porcelain insulator and preparation method thereof
By adding electrochromic materials and photosensitive resins to the surface coating of large-sized electroceramic insulators, the problem of strong concealment after breakdown of electroceramic insulators is solved, rapid fault identification and efficient fault handling are achieved, and insulators are improved under voltage Reliability and anti-fouling performance.
Patent Information
- Application Number
- CN202411352077.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
In the long run, the electroceramic insulators are highly concealed due to breakdown, and the troubleshooting takes a long time, the fault handling efficiency is low, and it may cause personal and property losses.
Large-size electroceramic insulators are used, and the surface coating contains electrochromic materials. After breakdown, the damage degree is observed according to the color depth, and the adhesion and weather resistance are improved through photosensitive resins and silane coupling agents, combining hydrophobic and oil-repellent The material is used to prevent flickering, forming excellent electrochromic and flickering properties.
Through the use of electrochromic composite coatings, the troubleshooting time is significantly shortened, the fault handling efficiency is improved, the reliability and anti-fouling performance of insulators under the action of voltage are enhanced, and the risk of personal and property losses is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of power transmission, and in particular to a large-size electric porcelain insulator and a preparation method thereof. Background Art
[0002] Porcelain insulators are a kind of porcelain electrical insulation material with good insulation and mechanical strength. They are made of natural minerals such as bauxite, kaolin, and feldspar as the main raw materials, fired at high temperature, and are specially used in power industry systems. Porcelain insulators not only have excellent electrical properties, but also have high environmental resistance (such as cold and heat, anti-pollution, aging, etc.), thus ensuring the stable operation of the power system.
[0003] During long-term operation, due to the service life of the insulator itself, the surface of the insulator deglazes and breaks down due to moisture, or the insulator breaks down under lightning overvoltage, operating overvoltage, or system overvoltage, causing the line to trip due to grounding fault. However, most insulators will not form pulverizing explosions after breakdown, and their appearance is normal. They are very hidden and the damage of the insulator cannot be directly observed. If a megohmmeter or DC tester is used for detection, not only will the troubleshooting take too long and the fault handling efficiency is too low, but it may also cause immeasurable personal and property losses due to excessive breakdown voltage. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a large-size electric porcelain insulator and a preparation method thereof. The electrochromic composite coating can change color after the electric porcelain insulator is broken down, and the degree of damage to the insulator can be directly observed according to the depth of the color, and corresponding measures can be taken to improve the efficiency of fault handling and shorten the time consumed for fault detection.
[0005] This application is implemented through the following technical solutions:
[0006] One of the purposes of the present application is to provide a large-sized electric porcelain insulator, comprising a ceramic part and a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following raw materials in parts by weight:
[0007] 30 to 50 parts of polytetrafluoroethylene, 5 to 10 parts of modified asphalt, 15 to 20 parts of photosensitive resin, 0.8 to 1.5 parts of photoinitiator, 20 to 30 parts of silica sol, 10 to 15 parts of nano-silicon dioxide, 5 to 9 parts of electrochromic material, 2 to 10 parts of silane coupling agent, 20 to 30 parts of organic solvent and 0 to 2 parts of auxiliary agent.
[0008] The large-sized electric porcelain insulator provided by the present application has a coating material containing an electrochromic material. After the electric porcelain insulator is broken down, the electrochromic composite coating on the surface of the electric porcelain insulator changes color under the action of voltage. The degree of damage to the insulator can be directly observed according to the depth of the color, and corresponding measures can be taken to improve the efficiency of fault handling and shorten the time consumed for fault troubleshooting. The coating contains hydrophobic (polytetrafluoroethylene, modified asphalt) and oleophobic (nano-silica) materials, so that the coating also has anti-fouling flashover performance, which can prevent the color change of the coating caused by non-electrical factors; the photosensitive resin can be polymerized and cured under the catalysis of ultraviolet light and photoinitiator, and the photosensitive resin improves the adhesion, hardness and weather resistance of the coating. The large-sized electric porcelain insulator provided by the present application has excellent electrochromic performance and anti-fouling flashover performance.
[0009] In some possible implementations, the electrochromic material is a transition metal oxide, including at least one of tungsten oxide, vanadium pentoxide, iridium oxide, and rhodium oxide.
[0010] In some possible implementations, the average particle size of the transition metal oxide is 210 nm to 500 nm.
[0011] In some possible implementations, the modified asphalt includes SBS modified asphalt and / or SEBS modified asphalt.
[0012] In some possible implementations, the coating has a thickness of 1 mm to 5 mm.
[0013] In some possible implementations, the specific surface area of the silica sol is 50 m 2 / g~90m 2 / g.
[0014] In some possible implementations, the pore volume of the silica sol is 1.1 cm 3 / g~1.5cm 3 / g.
[0015] In some possible implementations, the density of the silica sol is 2.0 g / cm 3 ~2.3g / cm 3 .
[0016] The second object of the present application is to provide a method for preparing the large-sized electric porcelain insulator provided in the present application, comprising the following steps:
[0017] The first mixed material and the second mixed material are mixed to obtain a premix; wherein the first mixed material includes polytetrafluoroethylene, modified asphalt, photosensitive resin, silane coupling agent and organic solvent; the second mixed material includes silica sol, nano silicon dioxide, silane coupling agent and electrochromic material;
[0018] Mixing the photoinitiator and the premix in a dark environment to obtain an electrochromic composite coating;
[0019] The electrochromic composite coating is coated on a large-sized electric porcelain insulator and subjected to a light curing treatment to obtain a coating.
[0020] The preparation method of the large-sized electric porcelain insulator provided by the present application comprises mixing a hydrophobic organic first mixture and an oleophobic inorganic second mixture, so that the organic raw materials and the inorganic raw materials can be fully and evenly mixed, wherein the silane coupling agent can promote the mixing of the first mixture and the second mixture; the organic solvent can inhibit the hydrolysis of the silane coupling agent, thereby avoiding the precipitation caused by the hydrolysis of the first mixture. A photoinitiator is mixed into the premix under light-proof conditions to avoid the polymerization of the photosensitive resin therein. Finally, a coating is formed on the large-sized insulator, and the large-sized electric porcelain insulator obtained has excellent electrochromic properties and anti-pollution flashover properties.
[0021] In some possible implementations, preparing the first mixture includes the steps of: adding polytetrafluoroethylene, modified asphalt, photosensitive resin and silane coupling agent to an organic solvent respectively under stirring conditions, and continuing to stir to obtain the first mixture.
[0022] In some possible implementations, preparing the second mixture includes the steps of: first mixing silica sol and silane coupling agent under ultrasonic conditions, then adding nano-silicon dioxide and electrochromic material respectively, and continuing ultrasonic dispersion to obtain the second mixture.
[0023] In some possible implementations, the light curing step includes:
[0024] The wet coating after coating is irradiated with ultraviolet light at 80° C. to 90° C. for 0.5 min to 5 min and then dried to obtain the coating.
[0025] In some possible implementations, the drying temperature is 100°C to 200°C. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0027] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0028] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0029] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0030] The term "large-size porcelain insulator" refers to porcelain insulators with larger sizes. This type of insulator is mainly used in power systems, especially in high-voltage, ultra-high-voltage and ultra-high-voltage power transmission fields, to isolate high-voltage live parts from grounded parts and realize insulation support and fixing functions.
[0031] Porcelain insulators need to be exposed to the natural environment for a long time during operation. When their service life reaches a critical point, the glaze on the surface of the insulator is severely peeled off and it is easy to be broken down by lightning, high voltage electricity and other electrical forces. Therefore, maintenance personnel need to be arranged to carry out maintenance at any time. If a megohmmeter or DC tester is used for detection, not only will the troubleshooting take too long and the fault handling efficiency is too low, but it may also cause immeasurable personal and property losses due to excessively high breakdown voltage.
[0032] At present, an irreversible color-changing ink layer is set on the outer surface of the electric porcelain insulator, but it is generally a temperature-sensitive material, which changes color when the temperature is within the color-changing range. The power workers can determine whether the insulator is damaged based on the color of the irreversible color-changing ink layer, reducing unnecessary troubles in the inspection work, facilitating timely discovery and replacement of insulators, and greatly improving the efficiency of the inspection work. However, this irreversible color-changing ink layer depends on temperature. If the ambient temperature is too high in summer, even if the electric porcelain insulator is not damaged, it will change color due to the high surface temperature of the electric porcelain insulator; if the ambient temperature is too low in winter, even if the electric porcelain insulator is damaged or the degree of damage is low, it is not enough to change the color of the color-changing ink, and the damage to the insulator cannot be directly observed.
[0033] In order to improve the efficiency and accuracy of fault handling of electric porcelain insulators, the embodiment of the present application proposes a large-size electric porcelain insulator and a preparation method thereof. The coating material contains an electrochromic material. After the electric porcelain insulator is broken down, the coating on the surface of the electric porcelain insulator changes color under the action of voltage. The degree of damage to the insulator can be directly observed according to the depth of the color, and corresponding measures can be taken to improve the efficiency of fault handling and shorten the time consumed for fault investigation. The coating has excellent electrochromic performance and anti-pollution flashover performance.
[0034] The following is a detailed description of a large-size electric porcelain insulator and a preparation method thereof according to an embodiment of the present application.
[0035]
Large size porcelain insulator
[0036] In a first aspect, an embodiment of the present application provides a large-size electric porcelain insulator, including a ceramic part, and also including a coating provided on the surface of the ceramic part, wherein the material of the coating includes the following raw materials in parts by weight:
[0037] 30 to 50 parts of polytetrafluoroethylene, 5 to 10 parts of modified asphalt, 15 to 20 parts of photosensitive resin, 0.8 to 1.5 parts of photoinitiator, 20 to 30 parts of silica sol, 10 to 15 parts of nano-silicon dioxide, 5 to 9 parts of electrochromic material, 2 to 10 parts of silane coupling agent, 20 to 30 parts of organic solvent and 0 to 2 parts of auxiliary agent.
[0038] The large-sized electric porcelain insulator provided in the embodiment of the present application has a coating material containing an electrochromic material. After the electric porcelain insulator is broken down, the electrochromic composite coating on the surface of the electric porcelain insulator changes color under the action of voltage. The degree of damage to the insulator can be directly observed according to the depth of the color, and corresponding measures can be taken to improve the efficiency of fault handling and shorten the time consumed for fault investigation. The coating contains hydrophobic (polytetrafluoroethylene, modified asphalt) and oleophobic (nano-silica) materials, so that the coating also has anti-fouling flashover performance, preventing the color change of the coating caused by non-electrical factors; silane coupling agent can promote electrochromic composite coating; photosensitive resin can be polymerized and cured under the catalysis of ultraviolet light and photoinitiator, and the photosensitive resin improves the adhesion, hardness and weather resistance of the coating. The large-sized electric porcelain insulator provided in the present application has excellent electrochromic performance and anti-fouling flashover performance.
[0039] In the embodiment, the weight percentage of polytetrafluoroethylene is 30 to 50 parts, which can be 30, 40, 50, or other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, polytetrafluoroethylene enables the electrochromic composite coating to have high heat resistance and cold resistance. Combined with modified asphalt, the electrochromic composite coating has excellent waterproof performance.
[0040] In the embodiment, the weight proportion of the modified asphalt is 5 to 10 parts, which can be 5, 8, 10, or other typical but non-limiting weight proportions or a range between any two weight proportions. In this case, the modified asphalt has excellent weather resistance and corrosion resistance. The synergistic effect with polytetrafluoroethylene makes the electrochromic composite coating have excellent waterproof performance.
[0041] In the embodiment, the weight proportion of the photosensitive resin is 15 to 20 parts, which can be 15, 18, 20, or other typical but non-limiting weight proportions or a range between any two weight proportions. In this case, the photosensitive resin rapidly polymerizes and solidifies under the action of ultraviolet light and a photoinitiator to form a hard coating, and the photosensitive resin coating has excellent wear resistance, weather resistance, and corrosion resistance. Combined with a silane coupling agent, the wear resistance of the electrochromic composite coating can be further improved and its service life can be extended.
[0042] In the embodiment, the weight percentage of the photoinitiator is 0.8 to 1.5 parts, which can be 0.8, 1.0, 1.5, or any other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the photoinitiator can accelerate the polymerization and curing of the photosensitive resin and shorten the curing time of the photosensitive resin.
[0043] In the embodiment, the weight percentage of silica sol is 20 to 30 parts, which can be 20 parts, 25 parts, 30 parts, etc., which are typical but non-limiting weight percentages, or a range between any two weight percentages. In this case, silica sol enables the electrochromic composite coating to have excellent film-forming properties and improves the protective performance of the coating.
[0044] In the embodiment, the weight percentage of nano silicon dioxide is 10 to 15 parts, which can be 10, 12, 15, or other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the oleophobicity of nano silicon dioxide makes it difficult for the coating formed by the electrochromic composite coating to absorb grease, and the electrochromic composite coating has excellent anti-fouling flashover performance in combination with polytetrafluoroethylene and modified asphalt.
[0045] In the embodiment, the weight of the electrochromic material is 5 to 9 parts, which can be 5, 7, 9, or other typical but non-limiting weights or a range between any two weights. In this case, the electrochromic material changes color when encountering a weak current, and the degree of damage to the corresponding insulator can be directly observed and judged according to the color change of different color-changing materials when encountering electricity, and corresponding measures can be taken to improve the efficiency of fault handling and shorten the time consumed for fault detection.
[0046] In the embodiment, the weight proportion of the silane coupling agent is 2 to 10 parts, which can be 2, 5, 10, or other typical but non-limiting weight proportions or a range between any two weight proportions. In this case, the silane coupling agent can promote the mixing of organic and inorganic materials in the raw materials of the electrochromic composite coating, so that the components of each raw material in the electrochromic composite coating are evenly dispersed.
[0047] In the embodiment, the weight percentage of the organic solvent is 20 to 30 parts, which can be 20 parts, 25 parts, 30 parts, etc., which are typical but non-limiting weight percentages, or a range between any two weight percentages. In this case, the organic solvent can be used as a solvent for hydrophobic raw materials such as polytetrafluoroethylene and modified asphalt, and the hydrophobic raw materials can be fully dispersed; in addition, the organic solvent can also inhibit the hydrolysis of the silane coupling agent, preventing the precipitation caused by its hydrolysis during the preparation process, thereby reducing the dispersion of the raw materials.
[0048] In the embodiment, the weight percentage of the auxiliary agent is 0 to 2 parts, which can be 0, 1, 2, or other typical but non-limiting weight percentages or any range between two weight percentages. In this case, the auxiliary agent stabilizes the properties of the coating.
[0049] In some embodiments, the length of the ceramic part is 13m to 18m and the diameter is 9m to 12m. In this case, the large-size porcelain insulator of the embodiment of the present application can be used in power systems, especially in the fields of high voltage, ultra-high voltage and ultra-high voltage transmission, to isolate high voltage live parts and grounded parts, and realize insulation support and fixing functions.
[0050] In some embodiments, the coating has a thickness of 1 mm to 5 mm, and in exemplary embodiments, it can be a typical thickness of 1 mm, 2 mm, 4 mm, 5 mm, or a range between any two thicknesses. In this case, the coating has electrochromic properties, anti-fouling flash properties, and a longer lifespan.
[0051] In some embodiments, the average molecular weight of polytetrafluoroethylene is 15,000 to 50,000. In exemplary embodiments, it can be 15,000, 30,000, 40,000, 50,000, or any other typical but non-limiting average molecular weight or a range between any two average molecular weights. In this case, the viscosity of polytetrafluoroethylene is low and it is easy to disperse, so that the electrochromic composite coating has better processing performance and coating uniformity.
[0052] In some embodiments, the modified asphalt includes SBS modified asphalt and / or SEBS modified asphalt. In this case, the modified asphalt enables the electrochromic composite coating to have excellent wear resistance, weather resistance and waterproof properties.
[0053] In some specific embodiments, the source of SBS modified asphalt includes at least one of BASF Group, Honeywell, Christian Chemical, and Mitsubishi Chemical.
[0054] In some specific embodiments, the source of SEBS modified asphalt includes at least one of Yueyang Petrochemical, Taiwan Rubber, Taiwan Ronghua, and Kraton, USA.
[0055] In some embodiments, the modified asphalt includes a mixture of SBS modified asphalt and SEBS modified asphalt, and the mass ratio of SBS modified asphalt to SEBS modified asphalt is (2-5):1. In the exemplary embodiment, it can be a typical but non-limiting mass ratio such as 2:1, 3:1, 4:1, 5:1, or a range between any two mass ratios. In this case, the viscosity of the mixture of SBS modified asphalt and SEBS modified asphalt is moderate, and it is easy to disperse and mix evenly with other raw materials.
[0056] In some embodiments, the photosensitive resin is a matte resin MA100 produced by eSUN. In this case, the matte resin MA100 has low viscosity, good fluidity, and is easy to mix with other raw material components.
[0057] In some specific embodiments, the photoinitiator includes at least one of benzoin, benzoin derivatives, benzophenone, and Michler's ketone. In this case, the photoinitiator accelerates the polymerization and curing of the photosensitive resin and shortens the curing time of the photosensitive resin.
[0058] In some embodiments, the specific surface area of the silica sol is 50 m 2 / g~90m 2 / g, in the example, it can be 50m 2 / g, 70m 2 / g, 90m 2 / g or any range between two specific surface areas. In some embodiments, the pore volume of the silica sol is 1.1 cm 3 / g~1.5cm 3 / g, in the example, it can be 1.1cm 3 / g, 1.3cm 3 / g, 1.5cm 3 / g or any range between two pore volumes. In some embodiments, the density of the silica sol is 2.0 g / cm 3 ~2.3g / cm 3 In the example, it can be 2.0g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 Typical but non-limiting densities or any range between two densities. In this case, the silica sol can contain enough nano-silica, silane coupling agent and electrochromic material to fully disperse these raw materials.
[0059] In some embodiments, the median particle size (D30) of the nano-silicon dioxide is 30 nm to 60 nm, and in the exemplary embodiment, it can be a typical but non-limiting median particle size of 30 nm, 40 nm, 60 nm, or a range between any two median particle sizes. In this case, the nano-silicon dioxide is easier to be evenly dispersed in the electrochromic composite coating, thereby improving the stability of the electrochromic composite coating.
[0060] In some embodiments, the electrochromic material is a transition metal oxide, including at least one of tungsten oxide, vanadium pentoxide, iridium oxide, and rhodium oxide. In this case, the metal elements in the transition metal oxide will undergo electronic transitions when encountering an electric field, thereby causing the color of the transition metal oxide to change significantly, for example, tungsten oxide changes from colorless to dark blue.
[0061] In some embodiments, the average particle size of the transition metal oxide is 210 nm to 500 nm. In the exemplary embodiment, the average particle size may be 210 nm, 300 nm, 500 nm, or any range between two average particle sizes. In this case, the transition metal oxide is easily dispersed evenly in the electrochromic composite coating, thereby improving the stability of the electrochromic composite coating.
[0062] In some embodiments, the silane coupling agent includes at least one of vinyl triethoxysilane (A-151), vinyl trimethoxysilane (A-171), γ-aminopropyl triethoxysilane (KH-550), N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane (KH-792), γ-glycidyloxypropyl trimethoxysilane (KH-560), and γ-methacryloxypropyl trimethoxysilane (KH-570). In this case, the silane coupling agent not only promotes the physical mixing between the organic raw material and the inorganic raw material, but KH-560 and KH-570 also react chemically with the photosensitive resin to enhance the bonding strength between the resin and the inorganic material.
[0063] In some embodiments, the organic solvent includes at least one of methanol, ethanol, acetone, and ethylene glycol. In this case, the organic solvent is easy to remove, has no impurities remaining, and has stable chemical properties.
[0064] In some embodiments, the auxiliary agent includes at least one of a defoamer and a leveling agent. In this case, the auxiliary agent improves the stability of the electrochromic composite coating.
[0065]
Method for preparing large-size porcelain insulators
[0066] A second aspect of the embodiment of the present application provides a method for preparing a large-size electric porcelain insulator provided in the embodiment of the present application, comprising the following steps:
[0067] S1. Mixing a first mixture and a second mixture to obtain a premix; wherein the first mixture includes polytetrafluoroethylene, modified asphalt, photosensitive resin, silane coupling agent and organic solvent; and the second mixture includes silica sol, nano-silicon dioxide, silane coupling agent and electrochromic material.
[0068] S2. Mix the photoinitiator and the premix in a dark environment to obtain an electrochromic composite coating.
[0069] S3. Apply the electrochromic composite coating on a large-sized electric porcelain insulator and perform a photocuring treatment to obtain a coating.
[0070] The preparation method of the large-sized electric porcelain insulator provided in the embodiment of the present application is to mix the hydrophobic organic first mixture and the oleophobic inorganic second mixture, so that the organic raw materials and the inorganic raw materials can be fully and evenly mixed, and the silane coupling agent therein can promote the mixing of the first mixture and the second mixture; the organic solvent can inhibit the hydrolysis of the silane coupling agent, thereby avoiding the precipitation caused by the hydrolysis of the first mixture. The photoinitiator is mixed into the premix under light-proof conditions to avoid the polymerization of the photosensitive resin therein. Finally, a coating is made on the large-sized insulator, and the large-sized electric porcelain insulator obtained has excellent electrochromic properties and anti-pollution flashover properties.
[0071] [Step S1]
[0072] In some embodiments, in the above step S1, preparing the first mixed material comprises the steps of:
[0073] Under stirring conditions, polytetrafluoroethylene, modified asphalt, photosensitive resin and silane coupling agent are added into the organic solvent respectively, and stirring is continued to obtain a first mixed material.
[0074] In the above preparation of the first mixture, there is no restriction on the order of adding polytetrafluoroethylene, modified asphalt, photosensitive resin and silane coupling agent, as long as the first mixture is mixed uniformly.
[0075] In some specific embodiments, when preparing the first mixed material, the stirring rate is 500 rpm to 950 rpm, and in the exemplary examples, it can be 500 rpm, 700 rpm, 900 rpm, 950 rpm, etc., which are typical but non-limiting rates, or a range between any two rates. In this case, the stirring rate can not only make the first mixed material uniformly mixed, but also reduce the adverse consequences such as bubbles generated during the mixing of the mixed material and the destruction of the structure.
[0076] In some specific embodiments, when preparing the first mixed material, the stirring time is 1 hour to 3 hours. In the exemplary embodiment, it can be a typical but non-limiting time such as 1 hour, 2 hours, 3 hours, or a range between any two times. In this case, continuing to stir after the raw materials are mixed can fully mix the first mixed material and improve the stability of the first mixed material.
[0077] In some specific embodiments, when preparing the first mixed material, the stirring method includes mechanical stirring or magnetic stirring. In this case, the mechanical stirring or magnetic stirring can not only stir the material with relatively high viscosity, but also make the material fully mixed and uniform.
[0078] In some embodiments, in the above step S1, preparing the second mixed material comprises the steps of:
[0079] Under ultrasonic conditions, the silica sol and the silane coupling agent are first mixed, and then the nano-silicon dioxide and the electrochromic material are added respectively, and ultrasonic dispersion is continued to obtain a second mixed material.
[0080] In the above-mentioned preparation of the second mixed material, the silica sol and the silane coupling agent are first mixed, and the silane coupling agent is attached to the surface of the silica sol, and then the inorganic nano-silicon dioxide and the electrochromic material are added, and the nano-silicon dioxide and the electrochromic material are fully dispersed in the mixture to form a stable second mixed material. By using ultrasonic dispersion, the nano-scale nano-silicon dioxide and the electrochromic material can fully enter the pores of the silica sol to achieve a uniform dispersion effect.
[0081] In some specific embodiments, when preparing the second mixed material, the ultrasonic power is 1000W to 2000W. In the exemplary embodiment, it can be a typical but non-limiting power such as 1000W, 1500W, 2000W, or a range between any two powers. In this case, the power can make the nano-silicon dioxide and the electrochromic material fully adsorbed and dispersed in the mixture of silica sol and silane coupling agent, and further make the second mixed material mixed uniformly.
[0082] In some specific embodiments, when preparing the second mixed material, the ultrasonic dispersion is continued for 1 hour to 3 hours. In the exemplary embodiment, it can be a typical but non-limiting time such as 1 hour, 2 hours, 3 hours, or a range between any two times. In this case, after the raw materials are mixed, the ultrasonic dispersion is continued, so that the second mixed material can be mixed more fully and the stability of the second mixed material can be improved.
[0083] In some embodiments, in the above step S1, the mass ratio of the silane coupling agent in the first mixture to the silane coupling agent in the second mixture is (0.5-2):1. In the exemplary embodiment, it can be a typical but non-limiting mass ratio such as 0.5:1, 1:1, 2:1, or a range between any two mass ratios.
[0084] In some embodiments, in the above step S1, the mixing step includes:
[0085] Under stirring conditions, the first mixed material and the second mixed material are mixed, and then an auxiliary agent is added and stirring is continued to obtain a premix.
[0086] In the above mixing process, the first mixed material and the second mixed material are stirred and mixed, so that the first mixed material and the second mixed material are fully mixed, and an auxiliary agent is added to remove foam generated during the stirring process, so as to obtain a premix with stable properties.
[0087] In some specific embodiments, the stirring rate is 1000 rpm to 1500 rpm, and in exemplary examples, it can be 1000 rpm, 1300 rpm, 1500 rpm, or any range between two rates. In this case, high-speed stirring can promote the full mixing of the first mixed material and the second mixed material.
[0088] In some specific embodiments, the stirring time is 15 minutes to 40 minutes. In the exemplary examples, it can be a typical but non-limiting time such as 15 minutes, 20 minutes, 30 minutes, 40 minutes, or a range between any two times. In this case, continuing to stir for a short time can make the raw materials fully mixed without destroying the structural properties of the premix.
[0089] In some specific embodiments, the stirring method includes mechanical stirring or magnetic stirring. In this case, the mechanical stirring or magnetic stirring can not only stir the material with relatively high viscosity, but also make the material fully mixed and uniform.
[0090] [Step S2]
[0091] In some embodiments, in the above step S2, the light-protected mixing condition can be conventional simple mixing, and there is no limitation, as long as the photoinitiator can be fully dispersed in the premix.
[0092] [Step S3]
[0093] In some embodiments, in the above step S3, the light curing step includes:
[0094] The wet coating after coating is irradiated with ultraviolet light at 80° C. to 90° C. for 0.5 min to 5 min and then dried to obtain a coating.
[0095] In the above-mentioned light curing treatment step, the photosensitive resin can be rapidly cured at 80°C to 90°C under ultraviolet light to form a dense and uniform coating, thereby improving the hardness, wear resistance, chemical resistance and weather resistance of the coating. Drying is used to remove volatile organic solvents in the coating.
[0096] In some specific embodiments, the wavelength of the ultraviolet light is 320 nm to 400 nm. In exemplary embodiments, it can be 320 nm, 330 nm, 380 nm, 400 nm, or other typical but non-limiting wavelengths or a range between any two wavelengths.
[0097] In some specific embodiments, the drying temperature is 100° C. to 200° C. In exemplary embodiments, it can be a typical but non-limiting temperature such as 100° C., 150° C., 200° C., or a range between any two temperatures.
[0098] In some specific embodiments, the drying time is 1 hour to 5 hours. In exemplary embodiments, the drying time may be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or other typical but non-limiting time or a range between any two times.
[0099]
application
[0100] A fifth aspect of the embodiments of the present application provides an application of a large-size electric porcelain insulator provided by the embodiments of the present application or a large-size electric porcelain insulator prepared by the method for preparing the large-size electric porcelain insulator provided by the embodiments of the present application in the field of power transmission and / or substation equipment.
[0101] The following is further described in conjunction with specific embodiments.
[0102] Example 1
[0103] Embodiment 1 proposes a large-sized electric porcelain insulator, including a coating, and also including a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following component raw materials in parts by weight:
[0104] 40 parts of polytetrafluoroethylene, 8 parts of SBS modified asphalt, 17 parts of matte resin MA100 (photosensitive resin), 1 part of benzophenone (photoinitiator), 25 parts of silica sol, 13 parts of nano-silica, 9 parts of tungsten oxide (electrochromic material), 7 parts of KH-560 (silane coupling agent), 25 parts of ethanol (organic solvent) and 1 part of defoaming agent (auxiliary agent); among them, the average molecular weight of polytetrafluoroethylene is 20,000, and the median particle size (D30) of nano-silica is 40nm.
[0105] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, comprising the following steps:
[0106] (1) Preparing a first mixture: adding polytetrafluoroethylene, SBS modified asphalt, matte resin MA100 and KH-560 into ethanol respectively under stirring condition of 700 rpm, and continuing stirring for 1.5 hours to obtain a first mixture.
[0107] (2) Preparation of the second mixture: First, the silica sol and the silane coupling agent were mixed under 1500W ultrasonic conditions, and then nano-silicon dioxide and tungsten oxide were added respectively, and ultrasonic dispersion was continued for 1 hour to obtain the second mixture.
[0108] (3) Mixing treatment: After mixing the first mixed material and the second mixed material at 1300 rpm, a defoaming agent was added and the mixture was stirred for 20 min to obtain a premix.
[0109] (4) Mixing in the dark: Mixing benzophenone and the premix in the dark to obtain an electrochromic composite coating.
[0110] (5) Applying the electrochromic composite coating on large-sized porcelain insulators.
[0111] (6) The wet coating was irradiated with ultraviolet light having a wavelength of 320 nm to 400 nm at 80° C. for 2 min and then dried at 100° C. for 1 h to obtain a coating with a thickness of 3 mm.
[0112] Example 2
[0113] Embodiment 2 proposes a large-sized electric porcelain insulator, including a coating, and also including a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following component raw materials in parts by weight:
[0114] 30 parts of polytetrafluoroethylene, 10 parts of SBS modified asphalt, 20 parts of matte resin MA100, 1.5 parts of benzophenone (photoinitiator), 20 parts of silica sol, 10 parts of nano-silica, 7 parts of tungsten oxide (electrochromic material), 8 parts of KH-560 (silane coupling agent), 20 parts of ethanol (organic solvent) and 1 part of defoaming agent (auxiliary agent); among them, the average molecular weight of polytetrafluoroethylene is 20,000, and the median particle size (D30) of nano-silica is 40nm.
[0115] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0116] Example 3
[0117] Embodiment 3 proposes a large-sized electric porcelain insulator, including a coating, and also including a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following component raw materials in parts by weight:
[0118] 45 parts of polytetrafluoroethylene, 5 parts of SBS modified asphalt, 15 parts of matte resin MA100, 0.8 parts of benzophenone (photoinitiator), 23 parts of silica sol, 12 parts of nano-silica, 5 parts of tungsten oxide (electrochromic material), 5 parts of KH-560 (silane coupling agent), 20 parts of ethanol (organic solvent) and 0.5 parts of defoaming agent (auxiliary agent); among them, the average molecular weight of polytetrafluoroethylene is 20,000, and the median particle size (D30) of nano-silica is 40nm.
[0119] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0120] Example 4
[0121] Embodiment 4 proposes a large-sized electric porcelain insulator, including a coating, and also including a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following component raw materials in parts by weight:
[0122] 50 parts of polytetrafluoroethylene, 5 parts of SBS modified asphalt, 20 parts of matte resin MA100, 1.5 parts of benzophenone (photoinitiator), 30 parts of silica sol, 15 parts of nano-silica, 9 parts of tungsten oxide (electrochromic material), 10 parts of KH-560 (silane coupling agent), 30 parts of ethanol (organic solvent) and 2 parts of defoaming agent (auxiliary agent); among them, the average molecular weight of polytetrafluoroethylene is 20,000, and the median particle size (D30) of nano-silica is 40nm.
[0123] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0124] Example 5
[0125] Embodiment 5 proposes a large-sized electric porcelain insulator, including a coating, and also including a coating arranged on the surface of the ceramic part, wherein the material of the coating includes the following component raw materials in parts by weight:
[0126] 35 parts of polytetrafluoroethylene, 10 parts of SBS modified asphalt, 20 parts of matte resin MA100, 1.5 parts of benzophenone (photoinitiator), 28 parts of silica sol, 11 parts of nano-silica, 8 parts of tungsten oxide (electrochromic material), 9 parts of KH-560 (silane coupling agent), 25 parts of ethanol (organic solvent) and 1.2 parts of defoaming agent (auxiliary agent); among them, the average molecular weight of polytetrafluoroethylene is 20,000, and the median particle size (D30) of nano-silica is 40nm.
[0127] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0128] Example 6
[0129] Example 6 proposes a large-sized electric porcelain insulator, the components and raw materials of which are basically the same as those of Example 1, except that the electrochromic material is vanadium pentoxide (which gradually changes from blue-green to orange-yellow after power is applied).
[0130] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0131] Example 7
[0132] Example 7 proposes a large-sized electric porcelain insulator, the components and raw materials of which are basically the same as those of Example 1, except that the electrochromic material is iridium oxide (which changes from transparent to blue-black after power is applied).
[0133] This embodiment also provides a method for preparing the large-size electric porcelain insulator provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0134] Comparative Example 1
[0135] Comparative Example 1 proposes a color-changing insulator, including a ceramic part, wherein an irreversible color-changing ink layer is provided on the outer surface of the ceramic part; the irreversible color-changing ink layer is composed of the following raw materials in the following weight percentages:
[0136] Mixed pigment 5% to 10%, emulsion 45% to 51%, titanium dioxide 7% to 15%, spiropyran thermosensitive microcapsules 18% to 29%, additives 12.5% to 25.8%, deionized water 6% to 14%, the sum of the mass percentages of the above components is 100%;
[0137] The mixed pigment is a mixture of polyethylene glycol with a molecular weight of 2000, poly(N,N-dimethylacrylamide), 4-aminobenzoic acid butyl and pigment powder, and the polyethylene glycol, poly(N,N-dimethylacrylamide), 4-aminobenzoic acid butyl and pigment powder are ground and blended in a mass ratio of 8:3:21:32;
[0138] Prepare the mixed pigment according to the following steps;
[0139] Weigh poly(N,N-dimethylacrylamide) (PDMA) and 4-aminobenzoic acid butyl in a mass ratio of 1:7 and mix to obtain component A;
[0140] Weigh polyethylene glycol with a molecular weight of 2000 and component A in a mass ratio of 1:3, and mix them to obtain component B;
[0141] Component B and pigment powder are weighed in a mass ratio of 1:1, and mechanically ground and blended to obtain a mixed pigment. The color of the mixed pigment is determined by the color of the pigment powder, and can be red, orange, yellow, green, blue, cyan, purple, etc.
[0142] The emulsion is a mixture of water-based acrylic soft emulsion, water-based acrylic hard emulsion and polyethylene wax emulsion. The percentage of each component in the emulsion to the total mass of the irreversible color-changing ink layer is: 30% to 35% of water-based acrylic soft emulsion, 15% to 20% of water-based acrylic hard emulsion, and 6% to 8% of polyethylene wax emulsion.
[0143] The additive is a mixture of a catalyst, a wetting agent, a dispersant and a defoaming agent. The percentage of each component in the additive to the total mass of the irreversible color-changing ink layer is: catalyst 2% to 5%, wetting agent 5% to 10%, dispersant 5% to 10%, and defoaming agent 0.5% to 0.8%.
[0144] The catalyst is one of manganese dioxide, chloroplatinic acid, NTCAT14, NTCAT16 and NTCAT102, the wetting agent is a nonionic surfactant, the dispersant is polyacrylate ammonium salt or polyacrylate sodium salt, and the defoamer is a mixture of polysiloxane or non-silicone amide and hydrocarbon.
[0145] The temperature of the temperature-sensitive point of the irreversible color-changing ink layer is 70°C. When the temperature of the irreversible color-changing ink layer is lower than 70°C, the irreversible color-changing ink layer appears pink. When the temperature of the irreversible color-changing ink layer is higher than 70°C, the irreversible color-changing ink layer appears colorless and remains unchanged.
[0146] When producing color-changing insulators, the outer surface of the ceramic parts is cleaned, and then the irreversible color-changing ink layer is applied and dried. The thickness of the irreversible color-changing ink layer is 3mm.
[0147] In order to verify the progressiveness of the large-size porcelain insulator and the preparation method thereof proposed in the embodiments of the present application, the large-size porcelain insulator of the embodiments of the present application and the color-changing insulator provided in the comparative example were respectively subjected to color-changing performance test, hydrophobicity test, flame retardant performance test, electrical breakdown test and surface flashover test.
[0148] Among them, (1) the content of the color change performance test is as follows:
[0149] 1) The coating of large-size porcelain insulators was tested using the KV-EC-7300 electrochromic device cycle test system of Zhuhai Kaiwei Optoelectronics Technology Co., Ltd. as follows: ① Perform 10,000 cycles of testing at a voltage of ±12kV to detect the light transmittance of the coating. ② Record the color change response time. ③ Observe whether the color change effect is obvious 100m after the coating changes color. The results are shown in Table 1 below.
[0150] 2) The color-changing insulator of comparative example 1 was placed in an oven for color-changing performance test: ① Because it is an irreversible color-changing ink, a cyclic test cannot be performed. ② The color-changing response time was recorded. ③ After the color-changing insulator changes color, observe whether the color-changing effect is obvious at 100m. The results are shown in Table 1 below.
[0151] (2) The hydrophobicity test of the irreversible color-changing ink of large-sized porcelain insulators or color-changing insulators was carried out using the standard IEC / TS62073-2003. The hydrophobicity of the large-sized porcelain insulators or color-changing insulators met the requirements.
[0152] (3) The flame retardant performance of the irreversible color-changing ink of large-sized porcelain insulators or color-changing insulators was tested using the standard GB / T 2408-2008. The flame retardant performance of the large-sized porcelain insulators or color-changing insulators met the requirements.
[0153] (4) The electrical breakdown test of the irreversible color-changing ink of large-sized porcelain insulators or color-changing insulators was carried out using standard HG / T 3330-2012. The results are shown in Table 1 below.
[0154] (5) Conduct a surface flashover test on the irreversible color-changing ink of large-sized porcelain insulators or color-changing insulators: apply a linearly increasing AC voltage of 5kV / s until the sample flashes along the surface, and record the surface flashover voltage value at this time. The sample is no longer used after flashing once, and a new sample is replaced for the second surface flashover voltage test. A total of 10 tests are conducted, and the 10 sets of test data are processed using a normal distribution, and the voltage value with a normal distribution percentage of 50% is taken as the final surface flashover voltage value. The results are shown in Table 1 below.
[0155] Table 1
[0156]
[0157] From Table 1 above, we can at least draw the following conclusions:
[0158] ① The color changing effect of the embodiment and the comparative example is obvious, because the coating of the large-sized electric porcelain insulator of the embodiment changes color to a dark color, while that of the comparative example changes color to a light color (pink).
[0159] ② The color change response time of the large-size porcelain insulator of the embodiment is shorter than that of the comparative example. This is because the comparative example is temperature-sensitive color change, and temperature change is a relatively slow process.
[0160] ③ After 10,000 cycles, the light transmittance of the large-sized porcelain insulator of the embodiment is still low, indicating that the coating of the large-sized porcelain insulator has good cycle stability.
[0161] ④ The surface flashover voltage and breakdown field strength of the embodiment are relatively high, indicating that the coating of the large-size porcelain insulator of the embodiment of the present application has excellent insulation performance.
[0162] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A large-size electric porcelain insulator, comprising a ceramic part, characterized in that: It also includes a coating disposed on the surface of the ceramic piece, wherein the material of the coating includes the following raw materials in parts by weight: 30 to 50 parts of polytetrafluoroethylene, 5 to 10 parts of modified asphalt, 15 to 20 parts of photosensitive resin, 0.8 to 1.5 parts of photoinitiator, 20 to 30 parts of silica sol, 10 to 15 parts of nano-silicon dioxide, 5 to 9 parts of electrochromic material, 2 to 10 parts of silane coupling agent, 20 to 30 parts of organic solvent and 0 to 2 parts of auxiliary agent.
2. The large-size electric porcelain insulator according to claim 1 is characterized in that: The electrochromic material is a transition metal oxide.
3. The large-size electric porcelain insulator according to claim 2 is characterized in that: The average particle size of the transition metal oxide is 210nm to 500nm.
4. The large-size electric porcelain insulator according to claim 1 is characterized in that: The modified asphalt includes SBS modified asphalt and / or SEBS modified asphalt.
5. The large-size electric porcelain insulator according to claim 1, characterized in that: The thickness of the coating is 1 mm to 5 mm.
6. The large-size electric porcelain insulator according to any one of claims 1 to 5, characterized in that: The specific surface area of the silica sol is 50m 2 / g~90m 2 / g; And / or, the pore volume of the silica sol is 1.1 cm 3 / g~1.5cm 3 / g; And / or, the density of the silica sol is 2.0 g / cm 3 ~2.3g / cm 3 .
7. A method for preparing a large-size electric porcelain insulator according to any one of claims 1 to 6, characterized in that: The steps include: The first mixed material and the second mixed material are mixed to obtain a premix; wherein the first mixed material includes polytetrafluoroethylene, modified asphalt, photosensitive resin, silane coupling agent and organic solvent; the second mixed material includes silica sol, nano silicon dioxide, silane coupling agent and electrochromic material; Mixing the photoinitiator and the premix in a dark environment to obtain an electrochromic composite coating; The electrochromic composite coating is coated on a large-sized electric porcelain insulator and subjected to a light curing treatment to obtain a coating.
8. The method for preparing a large-size electric porcelain insulator according to claim 7, characterized in that: The preparation of the first mixed material comprises the following steps: adding polytetrafluoroethylene, modified asphalt, photosensitive resin and silane coupling agent into an organic solvent respectively under stirring conditions, and continuing stirring to obtain a first mixed material; And / or, the preparation of the second mixture comprises the steps of: firstly mixing silica sol and silane coupling agent under ultrasonic conditions, then adding nano-silicon dioxide and electrochromic material respectively, and continuing ultrasonic dispersion to obtain the second mixture.
9. The method for preparing a large-size electric porcelain insulator according to claim 7 or 8, characterized in that: The light curing treatment step comprises: irradiating the wet coating after coating with ultraviolet light for 0.5min to 5min at 80°C to 90°C and then drying to obtain the coating.
10. The method for preparing a large-size electric porcelain insulator according to claim 9, characterized in that: The drying temperature is 100°C to 200°C.
